Peran Ilmu Manajemen Sarana Dan Prasarana Dalam Upaya Meningkatkan Kreativitas Generasi Milenial - Abai Tambunan; Esterlina Manalu (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2021)
Management science in facilitating the millennial generation in creativity, to get authentic and in-depth results using triangulation methods and using qualitative analysis with a case study approach that optimizes the role of the researcher as a key instrument, in this study, it was found that creativity of the millennial generation develops along with the availability of infrastructure, in the field of education, school management makes the science of infrastructure management as a stimulus for the creativity of students who are actually millennial groups.